The Relationship between Diet and Physical Activity with Nutritional Status in Adolescents at SMP Muhammadiyah 3 Samarinda - Armaniya Thasya Aprila; Supriadi B; Rieska Indah Mulyani (Formosa Journal of Multidisciplinary Research, 2023)
The need for nutrient intake and physical activity is needed for the growth and development of adolescents. The purpose of this study was to determine the relationship between diet and physical activity with the nutritional status of adolescents. The method used is a quantitative research design with a cross sectional approach. The population of this study were 54 students. Samples were taken using the total population. The analysis of this study used the Spearman test. The statistical test results showed a positive correlation was found between diet and nutritional status (p=0.000) and physical activity and nutritional status (p=0.000) meaning that there was a significant relationship. In conclusion, the relationship between diet and physical activity with the nutritional status of adolescents at SMP Muhammadiyah 3 Samarinda has a very strong relationship. If diet and physical activity are lacking, it will affect nutritional status and vice versa.